2021
DOI: 10.1002/jcb.30179
|View full text |Cite
|
Sign up to set email alerts
|

Genes controlling skeletal muscle glucose uptake and their regulation by endurance and resistance exercise

Abstract: Exercise improves the insulin sensitivity of glucose uptake in skeletal muscle. Due to that, exercise has become a cornerstone treatment for type 2 diabetes mellitus (T2DM). The mechanisms by which exercise improves skeletal muscle insulin sensitivity are, however, incompletely understood. We conducted a systematic review to identify all genes whose gain or loss of function alters skeletal muscle glucose uptake. We subsequently cross-referenced these genes with recently generated data sets on exercise-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 98 publications
(103 reference statements)
0
9
0
Order By: Relevance
“…Given that the 25 genes causally affect fibre proportions, functionally relevant DNA sequence variants that are related to these genes should affect human muscle fibre type proportions, provided that the function of these genes is conserved between mice and men. Together with a list of muscle hypertrophy genes [ 79 ], endurance genes [ 80 ], and glucose uptake genes [ 81 ] this additional list of causative genes should help to identify causative DNA variants that influence human sport and exercise-related traits [ 82 ] as well as human health—as many exercise-related traits are predictors of health.…”
Section: Discussionmentioning
confidence: 99%
“…Given that the 25 genes causally affect fibre proportions, functionally relevant DNA sequence variants that are related to these genes should affect human muscle fibre type proportions, provided that the function of these genes is conserved between mice and men. Together with a list of muscle hypertrophy genes [ 79 ], endurance genes [ 80 ], and glucose uptake genes [ 81 ] this additional list of causative genes should help to identify causative DNA variants that influence human sport and exercise-related traits [ 82 ] as well as human health—as many exercise-related traits are predictors of health.…”
Section: Discussionmentioning
confidence: 99%
“…The time taken to consume the meal (approximately 15 min) was replicated in subsequent conditions. At 3:30 into the experiment, participants were provided with a standardized lunch meal (beef rice, 250 mL lemon tea, and 48 g chocolate, consisting of 1100 kcal, where 69.4% energy from carbohydrate (187.9 g), 19.7% energy from fat (23.7 g), and 10.9% energy from protein (29.5 g)). During measurements, participants were allowed to use the internet, work on their computers, or read.…”
Section: Study Protocolmentioning
confidence: 99%
“…18 On the other hand, engaging in diverse muscle activities during both endurance and resistance exercises has been shown to enhance glucose uptake through distinct local pathways. 19 These various patterns of muscle activity, including factors like duration, amplitude, and the absence of contraction, can be effectively measured using wearable electromyography (EMG) devices. [20][21][22] A cross-sectional study has identified associations between EMG patterns, such as average EMG amplitude (aEMG) and EMG activity duration, and glucose metabolism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to elucidate the molecular mechanisms responsible for the ET effects [ 14 , 28 ], we identified the genes specifically modulated by ET in elderly muscle compared to young adults, and highlighted the importance of mitochondrial oxidative phosphorylation (OXPHOS) and extracellular matrix (ECM) remodeling in the skeletal muscle [ 16 , 24 , 57 , 59 ]. As shown in Figure 2 , the ET-induced genes in elderly men [ 16 , 24 , 57 , 59 ], SPARC , specifically binds several of the ECM molecules including the collagens [ 60 ]. Thus, they influence lamina organization by binding to the growth factors such as insulin-like growth factor 1 (IGF-1) and transforming growth factor beta 1 (TGF-β1) [ 61 , 62 , 63 ].…”
Section: Sparc -Mediated Effects Among the Exercise Benefitsmentioning
confidence: 99%